Biosiliceous and geochemical response to biotic and climatic events in the Palaeocene - Figus, Cécile; Bohaty, Steven M.; Renaudie, Johan; Witkowski, Jakub (Climate of the past, 2025)
Hyperthermal events are a key element in understanding Palaeogene climate history, but many of these events other than the prominent Palaeocene-Eocene Thermal Maximum are poorly understood and studied. Two hyperthermal events that occurred in the middle to late Palaeocene include the Latest Danian Event (LDE) and the Early Late Palaeocene Event (ELPE). Most studies of these events focus on calcareous nannofossils and foraminifera, as well as geochemical data and astronomical tuning, but, to date, none consider biosiliceous production and flux. We therefore present eight records of biosiliceous fluxes, supported by geochemical data, from the Atlantic, Pacific, and Indian ocean sites spanning parts of the Palaeocene. Our results show pronounced variability in biosiliceous fluxes through the Palaeocene, with a peak at the time of the LDE. Establishing a link between the ELPE and biosiliceous flux variability through this time interval is more challenging, but the occurrence of peaks in biosiliceous fluxes after this event may indicate a global response of biogenic silica to several short-term biotic events, including the ELPE.